Cooperative Learning An Innovative Practice for Enhancing Leadership and Decision-making Skills through Science Teaching - Thomas, Mary Vineetha; Kothari, R.G. (JOURNAL OF INDIAN EDUCATION, 2017)
In the present era of globalisation, where more stress is on a skilled workforce, opportunities for our students often depend as much on their communication and collaboration skills as they do on pure academic skills. This requires quality education and an important factor that affects the quality of education is the teaching-learning process. Quality management of the teaching-learning process demands innovative methods and experiments to be brought into our classrooms. It should focus on the all-round development of the learner. One such strategy promoting this aspect is Cooperative Learning (CL). CL has five essential elements: positive interdependence, face-to-face promotive interaction, individual accountability, appropriate use of collaborative skills and group processing. Collaborative skills include leadership skills, communication skills, trust-building skills, decision-making skills and skills of resolving conflicts. This paper focuses on how cooperative learning environment fosters development of collaborative skills of leadership and decision-making among Class 7 students through science teaching.